2021
DOI: 10.3390/ijerph18042163
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Differences in the Implementation of Smoke-Free Contracts—A Cross-Sectional Analysis from the School Randomized Controlled Trial X:IT

Abstract: Objective: The X:IT study is a school-based smoking preventive intervention that has previously been evaluated in a large randomized controlled trial (RCT) with good effects. However, the actual effect for participating students depends on the individual implementation. The aim of this study was to examine the implementation of smoke-free contract, which is one of the three main intervention components. Specifically, we examined whether it was implemented equally across family occupational social class (OSC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This shows that smokers were less likely to enter a stable 3-year contract. A Danish study also reported that students who smoked cigarettes were less likely to enter a contract in the first place (Bast et al, 2021 ). However, most of the questioned participants stated that the reason for not signing a contract was because they were never invited to sign a contract, alternatively that there was no specific reason (“I just didn’t do it”) (Bast et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This shows that smokers were less likely to enter a stable 3-year contract. A Danish study also reported that students who smoked cigarettes were less likely to enter a contract in the first place (Bast et al, 2021 ). However, most of the questioned participants stated that the reason for not signing a contract was because they were never invited to sign a contract, alternatively that there was no specific reason (“I just didn’t do it”) (Bast et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A Danish study also reported that students who smoked cigarettes were less likely to enter a contract in the first place (Bast et al, 2021 ). However, most of the questioned participants stated that the reason for not signing a contract was because they were never invited to sign a contract, alternatively that there was no specific reason (“I just didn’t do it”) (Bast et al, 2021 ). Both in our study and in the Danish study, girls were more likely to be in a (stable) contract, while in Sweden, the smoking prevalence is higher among girls compared to boys (Bast et al, 2021 ; Beeres et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the trial, we tested the effects of viewing the intervention on YCMC drinking behaviors (primary dependent variable), impacts on knowledge regarding the effects of alcohol on their disease and its management, and YCMC perceptions about the riskiness of drinking (putative intermediary variables). We also explored gender-based subgroup effects, given the potential that males and females might respond differently to the intervention [19,20]. All participants completed baseline and 6-month followup surveys; participants in the intervention arm also reported about knowledge and perceived risk of alcohol use immediately after viewing the intervention.…”
Section: Methodsmentioning
confidence: 99%